Pedagogical content knowledge of sustainability: A missing piece in the puzzle of professional development of educators in higher education for sustainable development. Issue 6 (4th September 2017) - Singer-Brodowski, Mandy
Abstract : Purpose: This paper's purpose is to describe students' learning processes in a project-based and self-organized seminar on sustainability. A detailed knowledge of typical learning processes is part of a pedagogical content knowledge of sustainability and can therefore contribute to the professional development of university educators. Design/methodology/approach: In a project-based and self-organized seminar, a case study has been conducted with the grounded theory's methodological approach. Data were collected from student interviews, group discussions and observations of students' planning and organization meetings. Findings: The results of the case study show that students' learning processes vary depending on their pre-seminar sustainability experiences. Two types have been established: sustainability newcomers and sustainability experts. Furthermore, the results indicate the importance of emotions in the involvement with sustainability. Research limitations/implications: The significance of the case study is limited by a small number of cases. Also, the results are specific for a seminar self-organized by the students and can therefore not simply be transferred to other seminars. Practical implications: Knowledge of specific learning processes and a possible conceptual change in sustainability classes could be an important issue in the professional development of university educators because it would increase the educators' pedagogical content knowledge. Originality/value: The triangulation of qualitative data mainly served the investigation of students' perspectives and therefore the understanding of subjective preferences, experiences and learning processes in the field of higher education for sustainable development (HESD).